Optimasi Dosis Pupuk Nitrogen dan Fosfor pada Bibit Kelapa Sawit (Elaeis guineensis Jacq. ) di Pembibitan Utama - Sudradjat Sudrajat; Anita Darwis; Ade Wachjar (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTThe total area of oil palm plantation has grown rapidly in Indonesia since the last three decades. Oil palm  extensification and replanting need high quality seedlings. Accurate rate of nitrogen and phosphor fertilizer are key factors to obtain high quality seedlings. The objective of this experiment was to determine the optimum rate of  nitrogen and phosphorus  fertilizers  for oil palm seedling (Elaeis guineensis Jacq.) in main nursery and to obtain seedlings ready for field planting. This experiment was carried out at IPB Experimental Station, Cikabayan Dramaga, Bogor, from November 2011 to May 2012. The experiment was arranged in a factorial randomized block design with three replications. The first factor was N i.e. 0, 8.51, 17.02, and 34.04 g N plant-1 and the second was P i.e. 0, 2.28, 4.56, and 9.12 g P plant-1. The result of the experiment showed that vegetative growth increased with fertilizer application. The height of plant were affected by interaction between N and P significantly. The total leave number and stem diameter increased quadratically with fertilizer rate of N and were linearly increased with application of P. Application of N fertilizer influenced the chlorophyl content only  at 5 months after planting, and did not significantly affect the stomatal density. The result of leaf analysis showed that nitrogen and phosphor content respectively were 3.43% and 0.28%, where  both of them were  above the critical level. The optimum rate of  N for oil palm seedling during six months at the main nursery was 20.06 g plant-1, whereas P was 4.24 g plant-1.Keywords: fertilizer recommendation, physiological respons, vegetative growth